The Lord of the rings - Zaentz, Saul; Bakshi, Ralph (Warner Home Video, 1978)
All the magical adventure of J.R.R. Tolkien's thrilling fantasy classic comes to life in this brilliantly animated tale of the enhanced land of Middle Earth - and the brave bans of hobbits, heroes and wizards who set out to protect it. When a dangerous and powerful magic Ring falls in to his hands, a little hobbit named Frodo is caught up in a gigantic adventure! Now, join him, the mighty wizard Gandalf and a daring band elves, dwarfs and warriors as they set out to defend their enchanted land from the wicked sorcerer who would destroy it. Set in a mystical age of magic, monsters and unlikely heroes on incredible journeys.